Possibility of chickpea autumn planting in Saravan condition - Mohsen Zafaranieh; Ahmad Nezami; Seyyed Masoud Ziaee; Mitra Jabbari (پژوهش‌های حبوبات ایران)
Long season and high temperature during spring in hot and dry areas has led to tendency for autumn planting. In order to evaluation of chickpea (Cicer arietinum L.) autumn planting possibility, a field experiment was done at the Agricultural Faculty and Natural Resources of Saravan Research Field in 2010. Experimental design was done as split plots based on randomized complete block design with three replications. The main plots and subplots included three planting dates (11 Oct., 2 Nov., 22 Nov), and five chickpea genotypes (MCC488, MCC208, MCC258, MCC770, MCC361), respectively. The effect of planting date on plant height, pod number per plant, seed number per plant, empty pods, 100-seed weight, biological and seed yield and harvest index was significant. The highest seed yield was achieved in first planting date (11 Oct.). Plant dry matter production and seed yield decreased with delaying of planting date. The effect of genotype on all measured parameters, was also significant (p≤ 0.05) and the genotype MCC361 had the highest seed yield (204 g.m-2). The interaction effect of planting date and genotype was significant and MCC361 had the highest seed yield (with average 255 g.m-2) at first planting date (11 Oct.) and the lowest yield was belong to genotype MCC 770 (17.55 g.m-2) at second planting date (22 Nov.). There were good correlation coefficient between seed yield with number of pod per plant (r= 0.84**), number of seed per plant (r= 0.63**), biological yield (r= 0.55**) and harvest index (r= 0.55**). Although the results showed that the autumn planting of chickpea in Saravan region has been successful, but to obtain more reliable results, continuation of these experiments and more accurate response to the winter chickpea planting is recommended.